PRODUCTION AND CHARACTERIZATION OF THE METAL OXIDE - ORGANO METALIC COMPOSITES BY HYDROTHERMAL METHOD - HAMAD, REKAWT (Fırat Üniveristesi, 2017)
Yapılan bu yüksek lisans tez çalışmasında amacımız yeni bir üretim yöntemi olan hidrotermal metod ile farklı kompozisyonlarda ZnO esaslı kompozit malzeme üretilmesidir. Elde edilen kompozit malzemelerin yapısal, morfolojik, optik ve elektriksel özellikleri araştırıldı. Bu incelemeler için sırasıyla; X-ışını kırınımı (XRD), taramalı elektron mikroskobu (SEM), Fourier transfrom infrared (FTIR), UV-VIS-NIR spektrofotometre ve iki prob yöntemi ölçümleri kullanıldı. Bileşimlerin analizleri enerji dispersive X-ray (EDX) analizi ile yapıldı. X-ışını analizleri ile yapıda difraksiyon veren düzlemler belirlendi, SEM analizleri ile tane yapısı belirlendi, FTIR analizleri ile yapısal bağlar incelendi. Optik ölçümler ile yasak bant aralığı hesaplandı ve elektriksel iletkenlik ölçümleri ile elektriksel iletkenlik değerleri hesaplandı.

In this master thesis, our aim is to produce composite material in different composition based on ZnO by hydrothermal method which is the new production method. Structural, morphological, optical and electrical properties of the obtained composite materials were investigated. For these examinations, respectively; (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FTIR), UV-VIS-NIR spectrophotometer and two probe method measurements. Chemical compositions of the compounds were determined by using energy dispersive X-ray (EDX). X-ray analysis revealed diffraction pattern in the structure, grain structure was determined by SEM analysis and structural bonds by FTIR analysis. Forbidden band gap was calculated by optical measurements and electrical conductivity were calculated by electrical conductivity measurements.
Hidrotermal metod ile metal oksit-organo metalik kompozitlerin üretilmesi ve karakterizasyonu
Keywords: Fizik ve Fizik Mühendisliği